Pengaruh Promosi, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Dimediasi Citra Merek Produk Halal Skincare Somethinc (Studi pada Mahasiswi FEB Universitas Islam Malang Tahun 2020) - Putri, Ambar Rizkiana; Rachma, N.; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study was conducted to determine the effect of promotion, price and product quality on purchasing decisions mediated by the brand image of Somethinc halal skincare products on FEB students at the Islamic University of Malang in 2020. this research uses explanatory research and a quantitative approach. The data source of this research is primary data obtained from answers to statements when distributing questionnaires to respondents who meet the criteria. The sampling technique used is non probability sampling with purposive sampling technique. The number of samples in this study were 115 respondents obtained from the Malhotra formula. to solve the problem in this study using the outer model test and inner model test with the help of data analysis using SmartPLS 4.0.9.9. The results of this study are promotion, price and product quality have a direct effect on brand image. promotion, price and brand image have a direct effect on purchasing decisions. promotion, price and product quality have an indirect effect on purchasing decisions mediated by brand image. while product quality has no direct effect on purchasing decisions. Keywords: Promotion, Price, Product Quality, Brand Image, Purchase Desicion